Entre a mãe e a avó: o nomadismo de mulheres idosas como tentativa de ruptura de arquétipos em Quarenta dias, de Maria Valéria Rezende - Vidal, Thalyta Costa (2025)
This paper analyzes nomadism as a form of displacement, both territorial and subjective, capable of shaping identities in symbolic and material ways. The research focuses on the work Quarenta Dias (2014), by Maria Valéria Rezende, and investigates how the nomadism experienced by elderly women, especially the character Alice, presents itself. To achieve the objectives, the theoretical contributions of Neumann (2021) are mobilized in the analysis of archetypes, complemented by the reflections of Delcastagné (2012), in addition to dialoguing with feminist criticism and gender studies. In the field of literary studies, the work is based on the ideas of Walter Benjamin (1989) on modernity and deterritorialization, as well as the contributions of Eagleton (2006) and Candido (2011) on the contemporary novel and its relationship with social structures. In order to develop the analysis, the study proposes three concepts: palimpsestic nomadism, extratextual nomadism and geographic nomadism.